Rare Incidental Finding on Torus Tubarius in Cone Beam CBCT Images - A Case Report - Suvendra Vijayan; Aarav Surapaneni; Shobena Jeevan Sethu; Anitha Potluri (Journal of Indian Academy of Oral Medicine and Radiology, 2025)
Soft tissue calcification and ossifications, which are abnormal deposition of calcium and phosphate salts, are common incidental findings in cone-beam computed tomography (CBCT). They are classified as dystrophic, metastatic, and idiopathic. Calcifications in the torus tubarius, which is the cartilaginous part of the eustachian tube (ET), are rare incidental findings in CBCT images. This case report showcases a rare instance of torus tubarius calcification in a 97-year-old female patient.